A new series of HCV inhibitors based on a 2-(thieno[2, 3b]pyridin-2-yl)-1, 3, 4-oxadiazole scaffold. Issue 46 (22nd April 2016) - Zuo, Wei-Qiong; Wang, Ning-Yu; Zhu, Yong-xia; Liu, Li; Xiao, Kun-Jie; Zhang, Li-Dan; Gao, Chao; Liu, Zhi-Hao; You, Xin-Yu; Shi, Yao-Jie; Peng, Cui-Ting; Ran, Kai; et al.
Abstract : A new series of HCV inhibitors based on a 2-(thieno[2, 3- b ]pyridin-2-yl)-1, 3, 4-oxadiazole scaffold was developed. Abstract : A new series of HCV inhibitors based on a 2-(thieno[2, 3- b ]pyridin-2-yl)-1, 3, 4-oxadiazole scaffold was developed. Detailed SAR investigations revealed the HCV inhibitory activity was sensitive to the size of C5, the C6-fused ring, and the size and flexibility of C5′ cycloalkane, which led to the identification of several compounds with potent inhibitory activity against HCV genotype 1b replicon. The most potent compound10d showed ∼100-fold improvement in potency compared with compound1, with an EC50 of 0.039 μM, but without obvious cytotoxicity in vitro .